STRUKTUR ORGANISASI PASCA KEBIJAKAN PENGHAPUSAN ESELON III-IV: STUDI KASUS PDDI LIPI - Rahma, Nurida Maulidia (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2020)
The dissolution of government institutions occurred again in the administration of President Joko Widodo in 2020. The policies taken by President Joko Widodo always have a background on budget efficiency and bureaucracy. The same thing also happened in October 2019. In the direction of the President in October 2019 it was stated that there was a need to simplify the bureaucracy. Simplification of the bureaucracy is intended to create a dynamic, agile, and professional bureaucracy that is effective and efficient. To achieve these objectives, it is necessary to change the organizational structure. The need to form an organizational structure is the background of this paper. In order for an organization to run effectively and efficiently, it is necessary to have an organizational structure that suits the needs and conditions of an organization. This paper uses a qualitative design with literature survey techniques and case studies in the Center for Data and Scientific Documentation of the Indonesian Institute of Sciences (PDDI LIPI). The output of this paper is a proposed organizational structure model that is in line with the current conditions of the PDDI LIPI and is considered for implementation in other public sector organizations.